2016
DOI: 10.3390/f7010017
|View full text |Cite
|
Sign up to set email alerts
|

Scientometrics of Forest Health and Tree Diseases: An Overview

Abstract: Abstract:Maintaining forest health is a worldwide challenge due to emerging tree diseases, shifts in climate conditions and other global change stressors. Research on forest health is thus accumulating rapidly, but there has been little use of scientometric approaches in forest pathology and dendrology. Scientometrics is the quantitative study of trends in the scientific literature. As with all tools, scientometrics needs to be used carefully (e.g., by checking findings in multiple databases) and its results m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 110 publications
0
6
0
1
Order By: Relevance
“…Over the last years, the disease caused by H. fraxineus has been studied intensively from a taxonomic, genetic, epidemiological and conservation biology perspective (Gross et al ., ; McKinney et al ., ; Mitchell et al ., ; Burokiene et al ., ; Muñoz et al ., ; Pautasso, ). However, there is still a need for an overview of evolutionary aspects of this topic.…”
Section: Introductionmentioning
confidence: 98%
“…Over the last years, the disease caused by H. fraxineus has been studied intensively from a taxonomic, genetic, epidemiological and conservation biology perspective (Gross et al ., ; McKinney et al ., ; Mitchell et al ., ; Burokiene et al ., ; Muñoz et al ., ; Pautasso, ). However, there is still a need for an overview of evolutionary aspects of this topic.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies on the topic have used different research databases to look for published papers, from Web of Science to Zoological Records, including those obtained from different research organizations (e.g., Birdlife International;De Lima et al, 2011;Ducatez and Lefebvre, 2014;McKenzie and Robertson, 2015). However, even if it has been highly recommended for this type of study (Pautasso, 2016), to our knowledge there has been only one attempt to investigate whether different databases might be offering similar conclusions in relation to research effort in birds (De Lima et al, 2011). In this case the authors found a positive correlation between the number of papers obtained from Web of Knowledge and those of the Birdlife International library catalog.…”
Section: Introductionmentioning
confidence: 99%
“…Ailleurs, quelques équipes demeurent encorea ctives en Europe et en Amérique du nord.C ette situation s'explique en grande partie parce que les ressources allouées àl ar echerche ont été affectées àl 'impact du changement climatique ou àd 'autres pathogènes émergents. Il est d'ailleurs curieux d'observer que toute nouvelle épidémie d'un agent pathogène exotique, comme la chalarose du frêne, entraîne une flambée soudaine des recherches sur de nouveaux pathosystèmes, ce qui ne peut que réduirel 'attention accordée àl ar echerche sur les nombreux autres risques liés àl as anté des arbres (Pautasso, 2016).…”
Section: Impactsur La Diversité Génétique Desormesunclassified